Commentary on Special Issue on Geriatric Assessment. (April 2018) - Molinari, Victor; Rosowsky, Erlene
We provide commentary about the articles in this special section of "Assessment in Older Adults" by using van Alphen's framework of a systematic multidimensional approach for diagnosis and treatment in older adults.